Did you hear about kitty karr? ebook A novel. - Paul, Crystal Smith (2023)
REESE'S BOOK CLUB PICK BOOK OF THE MONTH PICK A multigenerational saga that traverses the glamour of old Hollywood and the seductive draw of modern-day showbiz When Kitty Karr Tate, a White icon of the silver screen, dies and bequeaths her multimillion-dollar estate to the St. John sisters, three young, wealthy Black women, it prompts questions. Lots of questions. A celebrity in her own right, Elise St. John would rather focus on sorting out Kitty's affairs than deal with the press. But what she discovers in one of Kitty's journals rocks her world harder than any other brewing scandal could—and between a cheating fiancé and the fallout from a controversial social media post, there are plenty. The truth behind Kitty's ascent to stardom from her beginnings in the segregated South threatens to expose a web of unexpected family ties, debts owed, and debatable crimes that could, with one pull, unravel the all-American fabric of the St. John sisters and those closest to them. As Elise digs deeper into Kitty's past, she must also turn the lens upon herself, confronting the gifts and burdens of her own choices and the power that the secrets of the dead hold over the living. Did You Hear About Kitty Karr? is a sprawling page-turner set against the backdrop of the Hollywood machine, an insightful and nuanced look at the inheritances of family, race, and gender—and the choices some women make to break free of them.